2011
DOI: 10.1002/hed.21586
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA methyltransferase 1 in pharyngeal cancer related to treatment resistance

Abstract: DNMT1 may be a significant clinical predictor and a potential treatment strategy against head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, directly inhibiting STAT3 by STAT3 siRNA had no obvious effect on DNMT1 expression. Phosphorylation of Akt kinase has been reported to be the mechanism responsible for enhanced expression of DNMT1 stimulated by IL-6 [33], [34]. When we blocked phosphoinositide 3 kinase/Akt signaling using the specific inhibitor LY294002, the attenuation of AKT activation was associated with decreased DNMT1.…”
Section: Discussionmentioning
confidence: 88%
“…However, directly inhibiting STAT3 by STAT3 siRNA had no obvious effect on DNMT1 expression. Phosphorylation of Akt kinase has been reported to be the mechanism responsible for enhanced expression of DNMT1 stimulated by IL-6 [33], [34]. When we blocked phosphoinositide 3 kinase/Akt signaling using the specific inhibitor LY294002, the attenuation of AKT activation was associated with decreased DNMT1.…”
Section: Discussionmentioning
confidence: 88%
“…IL-6 secretion in oral squamous cancer is facilitated by the microenvironment, in particular by stromal derived factor-1 [29]. Moreover, numerous projects have demonstrated that IL-6- induced hypermethylation and gene silencing may be mediated by DNMTs [18], [20], [31][33]. Taken together, we proposed that chronic inflammation stress in the oral cavity may promote tumorigenesis mediated by increased IL-6 to induce aberrant DNA methylation via increased DNMT3b activity.…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that a switch to accumulating DNA hypermethylation may be caused by the overexpression of DNA methyltransferases 25. Epigenetic gene silencing, promoted by DNMTs, has been observed in various malignancies, supporting the claim that DNMT genes are overexpressed in human cancers and during cellular transformation 7, 13, 26, 27. It has been reported that DNMT3b participates in the carcinogenesis of several cancer types,19, 28, 29 but the role of DNMT3b in esophageal SCC requires further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…DNA methylation is typically mediated by DNA methyltransferases (DNMT); and, in mammalian genomes, there are 3 DNMT genes: DNMT3a and DNMT3b are responsible for de novo methylation and modify unmethylated DNA, and it is believed that DNMT1 is responsible for maintaining methylation patterns 10, 11. DNMT activity reportedly is increased in cancer cells and may be related to tumor aggressiveness and a poor prognosis 12‐14. Epigenetic silencing reported in gastric cancer and esophageal cancer is associated with overexpression of the DNMT family 5, 15, 16.…”
Section: Introductionmentioning
confidence: 99%